ALKAPRO.SITE: TRANSFORMATION OF EDUCATION AND MANAGEMENT AT MUHAMMADIYAH AL-KAUTSAR JUNIOR HIGH SCHOOL SPECIAL PROGRAM THROUGH DIGITAL SCHOOL IMPLEMENTATION - SYAHID, IBNU AMIRUS; PEMBANGUNAN, HELDY RAMADHAN PUTRA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Education has become more modern with the development of increasingly widespread technology. The practice can be internalized into the learning and school management system. This research aims to analyze the transformation of education and management through implementing digital school in Muhammadiyah Al-Kautsar Junior High School Special Program. This research is a descriptive qualitative research with a field research method. The data collection methods used are in-depth interviews and observations. The research results show that Muhammadiyah Al-Kautsar Junior High School Special Program has demonstrated significant steps in creating digital transformation in learning and its management system. The implementation of this technology experienced obstacles in internet network connectivity and the readiness of supporting infrastructure due to the limited budget provided. Internalization of technology in learning improves accessibility and student learning experience. Meanwhile, the management system can be more efficient and effective, making it easier to administer and transparent data management. Parents and teachers are given convenience in monitoring the development of each student. The school continues to strive to ensure the development of students holistically, both in technological skills and the cultivation of moral values. This research makes an essential contribution to understanding the digital transformation process in schools. The implications of this research can be used as a guide and evaluation material to optimize the digitalization process of educational institutions in Indonesia. ABSTRAKPendidikan menjadi semakin modern seiring dengan perkembangan teknologi yang semakin luas. Praktik tersebut dapat diinternalisasikan ke dalam sistem pembelajaran dan manajemen sekolah. Penelitian ini bertujuan untuk menganalisis transformasi pendidikan dan manajemen melalui penerapan sekolah digital di Program Khusus SMP Muhammadiyah Al-Kautsar. Penelitian ini merupakan penelitian kualitatif deskriptif dengan metode penelitian lapangan. Metode pengumpulan data yang digunakan adalah wawancara mendalam dan observasi. Hasil penelitian menunjukkan Program Khusus SMP Muhammadiyah Al-Kautsar telah menunjukkan langkah signifikan dalam menciptakan transformasi digital dalam pembelajaran dan sistem pengelolaannya. Penerapan teknologi ini mengalami kendala pada konektivitas jaringan internet dan kesiapan infrastruktur pendukung karena terbatasnya anggaran yang disediakan. Internalisasi teknologi dalam pembelajaran meningkatkan aksesibilitas dan pengalaman belajar siswa. Sementara itu, sistem pengelolaannya bisa lebih efisien dan efektif, sehingga memudahkan pengadministrasian dan pengelolaan data secara transparan. Orang tua dan guru diberikan kemudahan dalam memantau perkembangan setiap siswa. Sekolah terus berupaya untuk menjamin perkembangan peserta didik secara holistik, baik dalam keterampilan teknologi maupun penanaman nilai-nilai moral. Penelitian ini memberikan kontribusi penting untuk memahami proses transformasi digital di sekolah. Implikasi penelitian ini dapat dijadikan pedoman dan bahan evaluasi untuk mengoptimalkan proses digitalisasi lembaga pendidikan di Indonesia.